Analisis Dan Perancangan Sistem Informasi Penjualan Pada Toko Cenhsin Street - Levina, Fransiska; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2021)
The Cenhsin Street store is a shop that specializes in selling merchandise. But in selling so many goods, the sales system is still using sales. The purpose of this study is to analyze and design sales information systems, including making it easier to sell products, record sales transactions, search for goods and make reports. Modeling system is using UML (Unified Modeling Language) consisting of Use Case Diagrams, Activity Diagrams and Class Diagrams, with the design of a prototype. This research resulted in a prototype of a sales information system that was able to assist Cenhsin Street stores in carrying out operational activities. In further development, it is expected that this sales information system can have a more attractive appearance.